2019
DOI: 10.3390/vaccines7030096
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Protection Efficacy of a Naked Self-Replicating mRNA-Based Zika Virus Vaccine

Abstract: To combat emerging infectious diseases like Zika virus (ZIKV), synthetic messenger RNAs (mRNAs) encoding viral antigens are very attractive as they allow a rapid, generic, and flexible production of vaccines. In this work, we engineered a self-replicating mRNA (sr-mRNA) vaccine encoding the pre-membrane and envelope (prM-E) glycoproteins of ZIKV. Intradermal electroporation of as few as 1 µg of this mRNA-based ZIKV vaccine induced potent humoral and cellular immune responses in BALB/c and especially IFNAR1-/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 60 publications
(82 reference statements)
3
57
0
1
Order By: Relevance
“…Evidently, a strong type I IFN mediated inflammatory response should also be avoided when synthetic mRNAs are considered for protein-replacement therapy, gene editing or stem cell reprogramming [25,26]. In line with previous reports [8,11,15], we found that intradermal electroporation of our formerly developed ZIKVac-sa-mRNA vaccine results in a very rapid upregulation of type I IFNs, with a maximal induction within 5 hours after sa-mRNA administration (Fig. 2).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Evidently, a strong type I IFN mediated inflammatory response should also be avoided when synthetic mRNAs are considered for protein-replacement therapy, gene editing or stem cell reprogramming [25,26]. In line with previous reports [8,11,15], we found that intradermal electroporation of our formerly developed ZIKVac-sa-mRNA vaccine results in a very rapid upregulation of type I IFNs, with a maximal induction within 5 hours after sa-mRNA administration (Fig. 2).…”
Section: Discussionsupporting
confidence: 87%
“…However, our data do not support this idea, as the peak in IFN-β production occurs directly after the delivery of the sa-mRNA and thus not at the moment of sa-mRNA replication. Moreover, we recently reported a similar IFN-β induction for replication-deficient and replication-competent sa-mRNAs in mice [15].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations